2015
DOI: 10.1038/sj.bdj.2015.99
|View full text |Cite
|
Sign up to set email alerts
|

The contents of dental implant patient information leaflets available within the UK

Abstract: Purpose: Patient information leaflets are designed to provide easy to follow information summaries and first point of contact information about treatment options. This survey reviewed the content of dental implant patient information leaflets, produced by implant companies and available within the UK in 2011.Methods: Dental implant companies in the UK were asked to provide samples of their patient information leaflets. The information within the leaflets was then summarised as well as the quantity, the types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The leaflet was however regarded by patients as generic and inadequate to inform their personal need of information necessary for the decision‐making process of implant treatment. Patients’ reflection on the leaflet in this study was similar to previous findings which doubted the quality of information and illustration provided in implant leaflets in the UK (Barber et al., ). Whilst a generic written leaflet can deliver basic information (Barber et al., ), patients were interested in receiving written information that is personalised and addresses their particular clinical situations, treatment options and deal with their particular concerns.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The leaflet was however regarded by patients as generic and inadequate to inform their personal need of information necessary for the decision‐making process of implant treatment. Patients’ reflection on the leaflet in this study was similar to previous findings which doubted the quality of information and illustration provided in implant leaflets in the UK (Barber et al., ). Whilst a generic written leaflet can deliver basic information (Barber et al., ), patients were interested in receiving written information that is personalised and addresses their particular clinical situations, treatment options and deal with their particular concerns.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, dentists seem to be the main source of implant information in places such as Hong Kong (Yao et al., ), yet doubts have been reported concerning the quality of the information provided during clinical consultation (Pommer et al., ; Simensen, Bøe, Berg, & Leknes, ; Yao et al., ). Another popular source of patients’ information is written leaflets, which may not always be of high quality or include comprehensive content (Barber, Puryer, McNally, & O'Sullivan, ). Recently, the Internet and social media are also increasingly contributing to patients’ knowledge and frequently accessed by patients to search for information about dental implant treatments (Atieh, Morgaine, & Duncan, ; Yao et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The nystagmus information pack includes details about infantile and acquired nystagmus. The advantages and disadvantages (Barber et al 2015) of different management options, with the aim of providing balanced information, is also provided. Patients with a range of different types of nystagmus, their families and orthoptists have been involved in the development of the nystagmus information pack, as patient involvement has been highlighted as important in other areas of healthcare (McIntosh and Shaw 2003).…”
Section: Developing Standardised Patient Information About Nystagmusmentioning
confidence: 99%
“…Initiatives involving the provision of patient information based on a patient-centred approach that emphasises the priorities and needs of patients rather than an assumption of patient compliance or passivity ( Fahrenfort 1987 ; Dixon-Woods 2001 ) have been associated with better patient outcomes ( Barlow, Turner and Wright 1998 ; Clark and Nothwehr 1997 ; Brown 1998 ; McIntosh and Shaw 2003 ). The use of patient information has been studied in a variety of healthcare services, including dentistry ( Barber et al 2015 ), urology ( Joshi et al 2001 ), breast cancer ( Dey 2004 ), paediatric oncology ( James et al 1988 ), diabetes ( Hardy, O’Brien and Furlong 2001 ), stroke ( Mant et al 1998 ) and general practice ( Ley 1988 ). An evaluation of 23 different sources of patient information in dental care found that insufficient information about the disadvantages of treatment was included, leading to a failure to provide sufficient detail for gaining informed consent ( Barber et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation